Financial Literacy's Influence on The Effectiveness of QRIS Use among MSME Owners in Indonesia: The Mediating Role of Financial Behavior - Evelin Sutrisno; Roma Nainggolan (LP3M Universitas Putra Bangsa, 2025)
Financial literacy is a key factor in managing the finances of MSMEs. The rapid growth in the adoption of QRIS in Indonesia reflects its extensive use and its influence on the financial behavior of MSME owners. This research seeks to explore the impact of financial literacy on the effectiveness of QRIS use, with financial behavior acting as a mediating variable among MSME owners in Indonesia. The study population encompasses all Micro, Small, and Medium Enterprise (MSME) owners across Indonesia who utilize QRIS as a payment method. The sample size was determined using the Structural Equation Model (SEM) technique, and purposive sampling was employed, targeting MSME owners who have integrated QRIS into their operations, whether for the sale of goods or services. The results demonstrate that financial literacy has a significant effect on the successful use of QRIS, with financial behavior playing a mediating role.